Wie korrekt sind die Nachfragedaten des Straßenverkehrs? Eine kritische Betrachtung der mehrfach revidierten Fahrleistungsstatistik. - Hunsicker, Frank; Knie, Andreas; Lange, Günter (Deutscher Verkehrs-Verl., 2007)
Angaben zu Aufkommen und Verkehrsleistung stellen eine unverzichtbare Grundlage zur Einordnung der am Mobilitätsmarkt beteiligten Verkehrsträger dar. Die Politik ist ebenso auf eine solide Grundlage des Verkehrsmarktvolumens und der Nachfrageverhältnisse angewiesen wie Wirtschaft und Wissenschaft. difu

Important transport policy-related decisions tend to be based on published transport statistics and consequential traffic forecasts - e.g. for infrastructure expansion. The outline data at hand should, therefore, be transparent from the aspect of methodology and not give cause to controversy. This is apparently not the case with regard to the recently revised performance statistics for individual motorized traffic since, at the time of compilation, it has been necessary to rely on an incomplete census, estimates and extrapolation. The unreliability of these statistics relates especially to fuel imports, average consumption, recalculated traffic results and the lack of economic plausibility of the data shown. In view of the doubtfulness expressed about the quantity, quality and periodicity of the data at hand, there is a need for an empirically improved and reliable data base. difu
Keywords: Verkehr; Verkehrsplanung; Straßenverkehr; Verkehrsnachfrage; Verkehrsprognose; Verkehrsstatistik; Erhebung; Fahrleistung